Translated and Adapted – The Influence of Time on Translation - Rossi, Paula (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2003)
AbstractIn this paper I will examine how the fairytales written by Zachris Topelius, the famous 19th century Finnish storyteller, were translated into Finnish and into English at different times. The fairytales contain Topelius’ personal ideals of upbringing, biblical and religious as well as moral and educational elements, for instance. The authors of the more recent translations have considered it necessary to modify the source texts so that they would be more accessible to today’s children than the earlier Finnish translations. In my analysis, I focus on the translational choices made by the translators.